Inflammatory biomarkers at different stages of Sarcopenia in older women - da Costa Teixeira, Leonardo Augusto; Avelar, Nubia Carelli Pereira; Peixoto, Marco Fabrício Dias; Parentoni, Adriana Netto; Santos, Jousielle Marcia dos; Pereira, Fabiana Souza Máximo; Danielewicz, Ana Lúcia; Leopoldino, Amanda Aparecida Oliveira; Costa, Sabrina Paula; Arrieiro, Arthur Nascimento; Soares, Luana Aparecida; da Silva Lage, Vanessa Kelly; et al. (Scientific Reports, 2023)
In recent years, studies have found that Sarcopenia alters inflammatory biomarkers. However, the behavior of inflammatory biomarkers at different stages of Sarcopenia is not well understood. This study aimed to compare a broad panel of inflammatory biomarkers in older women at different stages of Sarcopenia. The study included 71 Brazilian community-dwelling older women. Muscle Strength was assessed by using handgrip strength (Jamar dynamometer). The Short Physical Performance Battery (SPPB) was performed to assess the physical performance, and body composition was assessed by DEXA. Sarcopenia was diagnosed and classified according to the EWGSOP2 criteria. Blood was drawn, and inflammatory biomarkers associated with Sarcopenia (IL-2, IL-4, IL-5, IL-6, IL-8, IL-10, TNF, adiponectin, leptin, resistin, BDNF, sTNFr-1 and sTNFr-2) was analysed. After diagnosis and classification of sarcopenia, 45% of women did not present Sarcopenia (NS, N = 32), 23.9% were diagnosed with Sarcopenia Probable (SP, N = 17), 19,7% with Sarcopenia Confirmed (SC, N = 14), and 11.3% with Severe Sarcopenia (SS, N = 8). The analysis of inflammatory biomarkers revealed that the more advanced the stage of Sarcopenia, the higher the levels of BDNF, IL-8, sTNFr-1, and sTNFr-2. The assessment of BDNF, IL-8, sTNFr-1, and sTNFr-2 levels may be an adjuvant tool in diagnosis and severity classification of Sarcopenia in older Brazilian women.
Number: 1
Keywords: Biomarkers; Cytokines; Diagnostic markers; Diseases; Endocrine system and metabolic diseases; Endocrinology; Epidemiology; Medical research; Predictive markers